Critical pathomechanisms of NSAID-exacerbated respiratory disease (N-ERD) clarified by treatment with omalizumab, an anti-IgE antibody - Hiroaki Hayashi; Makoto Ishii; Yoshinori Hasegawa; Masami Taniguchi (Allergology International)
Characteristic symptoms of NSAID-exacerbated respiratory disease (N-ERD) include asthma, chronic eosinophilic rhinosinusitis with nasal polyposis, cysteinyl LT (CysLT) overproduction and NSAIDs hypersensitivity. Some N-ERD patients present with episodic treatment-resistant extra-respiratory symptoms (CysLT-associated coronary artery vasospasm, gastroenteritis, or skin rash). Even when using standard treatments for respiratory and extra-respiratory symptoms, including systemic corticosteroids and aspirin desensitization, it is difficult to control the clinical symptoms and severe type 2 inflammation involved with mast cells, eosinophils, ILC2s, and platelet activation. Few treatment options are applicable in a clinical setting. Therefore, identifying effective treatments is essential for managing N-ERD patients who suffer from these conditions. Our previous observational study demonstrated 12-month omalizumab treatment of N-ERD was clinically effective against respiratory symptoms. Despite the remaining eosinophilia, omalizumab significantly reduced urinary LTE4 and PGD2 metabolites to near normal levels at steady state. Based on the preliminary study, we demonstrated that omalizumab induced tolerance to aspirin in N-ERD patients 3 months after therapy initiation and suppressed activation of mast cells during 24 h of initiation in a randomized manner. Moreover, omalizumab had significant efficacy against extra-respiratory symptoms at baseline (lacking aspirin exposure) as well as throughout aspirin challenge. This review addresses the latest discoveries related to N-ERD pathogenesis and the significant effectiveness of omalizumab on N-ERD as a mast cell stabilizer. Our findings regarding omalizumab-associated mast cell inhibitory effects are indirect evidence that mast cell dysregulation and, possibly, IgE are pivotal components of N-ERD.